Characteristics of Surface “Melt Potential” over Antarctic Ice Shelves based on Regional Atmospheric Model Simulations of Summer Air Temperature Extremes from 1979/80 to 2018/19 - Orr, Andrew; Deb, Pranab; Clem, Kyle R.; Gilbert, Ella; Bromwich, David H.; Boberg, Fredrik; Colwell, Steve; Hansen, Nicolaj; Lazzara, Matthew A.; Mooney, Priscilla A.; Mottram, Ruth; Niwano, Masashi; et al. (Journal of Climate, 2023)
We calculate a regional surface “melt potential” index (MPI) over Antarctic ice shelves that describes the frequency (MPI-freq; %) and intensity (MPI-int; K) of daily maximum summer temperatures exceeding a melt threshold of 273.15 K. This is used to determine which ice shelves are vulnerable to melt-induced hydrofracture and is calculated using near-surface temperature output for each summer from 1979/80 to 2018/19 from two high-resolution regional atmospheric model hindcasts (using the MetUM and HIRHAM5). MPI is highest for Antarctic Peninsula ice shelves (MPI-freq 23%–35%, MPI-int 1.2–2.1 K), lowest (2%–3%, <0 K) for the Ronne–Filchner and Ross ice shelves, and around 10%–24% and 0.6–1.7 K for the other West and East Antarctic ice shelves. Hotspots of MPI are apparent over many ice shelves, and they also show a decreasing trend in MPI-freq. The regional circulation patterns associated with high MPI values over West and East Antarctic ice shelves are remarkably consistent for their respective region but tied to different large-scale climate forcings. The West Antarctic circulation resembles the central Pacific El Niño pattern with a stationary Rossby wave and a strong anticyclone over the high-latitude South Pacific. By contrast, the East Antarctic circulation comprises a zonally symmetric negative Southern Annular Mode pattern with a strong regional anticyclone on the plateau and enhanced coastal easterlies/weakened Southern Ocean westerlies. Values of MPI are 3–4 times larger for a lower temperature/melt threshold of 271.15 K used in a sensitivity test, as melting can occur at temperatures lower than 273.15 K depending on snowpack properties.
Keywords: Antarktis; glasiologi; klima; smelting

Insignificant change in Antarctic snowfall since the International Geophysical Year - Monaghan, Amdrew J; Bromwich, David H; Fogt, Ryan L; Wang, Sheng-Hung; Mayewski, Paul A; Dixon, Daniel A; Ekaykin, Alexey; Frezzotti, Massimo; Ian Goodwin, Ian; Isaksson, Elisabeth; Kaspari, Susan D; Morgan, Vin I; et al. (Science, 2006)
Keywords: Antarktis; glasiologi